No association between major congenital malformations and exposure to Kampo medicines containing rhubarb rhizome: A Japanese database study - Suzuki, Satoko; Obara, Taku; Ishikawa, Tomofumi; Noda, Aoi; Matsuzaki, Fumiko; Arita, Ryutaro; Ohsawa, Minoru; Mano, Nariyasu; Kikuchi, Akiko; Takayama, Shin; Ishii, Tadashi (Frontiers in Pharmacology, 2023)
Traditional Japanese (Kampo) medicines containing rhubarb rhizome are prescribed for constipation during pregnancy; however, detailed safety information of their use for pregnant women is lacking. The aim of current study was to clarify the association between prescription Kampo-containing rhubarb rhizome (KRR) in the first trimester of pregnancy and congenital malformations in newborns. Using a large Japanese health insurance claims database, we included pregnant women who enrolled the same health insurance society from 3 months before pregnancy to the delivery date, who gave birth between 2010 and 2019, and those with data related to their infants. Pregnant women who were prescribed magnesium oxide (MgO), commonly used for constipation, during the first trimester of pregnancy and their infants were extracted as controls. Associations between KRR prescribed in the first pregnancy trimester and major congenital malformations (MCM) in the infants were examined using multivariate logistic regression analysis. Of 75,398 infants, 4,607 (6.1%) were diagnosed with MCMs within the first year after birth. Furthermore, 9,852 infants were born to women prescribed MgO, among whom 680 (6.9%) had MCMs; 450 infants were born to women prescribed KRR, among whom 28 (6.2%) had MCMs. Multivariate logistic regression analysis identified no difference in MCM risk between the two types of prescriptions [crude odds ratio (OR) 0.895, 95% confidence interval (CI) 0.606–1.322, adjusted OR 0.889, 95% CI 0.599–1.320]. In conclusion, the risk of MCMs did not differ between those prescribed KRR or MgO in the first trimester of pregnancy.